Successful therapy in post-transplant lymphoproliferative disorder after allogeneic haematopoietic stem cell transplantation in resistant Hodgkin’s disease - Krenska, Anna; Styczyński, Jan; Dębski, Robert; Pogorzała, Monika; Małkowski, Bogdan; Wysocki, Mariusz (Contemporary Oncology/Współczesna Onkologia, 2009)
It has been shown recently that allogeneic haematopoietic stem cell transplantation (HSCT) can be considered as a clinical option in the treatment of refractory and relapsed Hodgkin’s disease. However, potent T-cell immunosuppression predisposes to the development of post-transplant lymphoproliferative disorder (PTLD) in patients after HSCT. Other well-know risk factors for development of post transplant lymphoproliferative disorder (PTLD) include unrelated or mismatched SCT, T-cell depletion, use of ATG or OKT3, and also HLA mismatch/T-cell depletion, EBV serology mismatch between donor and recipient and splenectomy. The higher the number of risk factors, the higher the frequency of EBV reactivation. We present a case of a patient with refractory Hodgkin’s disease, who relapsed after autologous HSCT, and subsequently was referred for allogeneic HSCT. At day +90 after transplantation, clinical symptoms of EBV-PTLD developed, and were confirmed by PCR (EBV-DNA-emia), biopsy and positron emission tomography (CT-PET). The patient was treated with 8 cycles of rituximab and reduction of immunosuppression (RI). Monitoring of the treatment was performed by PCR detection of EBV-DNA and CT-PET scan. Due to the absence of graft- versus -host disease (GVHD) symptoms, donor-lymphocyte infusion (DLI) was done, followed by development of GVHD symptoms. One year after allo-HSCT, the patient remains in complete remission, confirmed by negative CT-PET scan and EBV-DNA-emia. In conclusion, allo-HSCT, supported by DLI, might be an effective therapy in refractory/relapsed Hodgkin’s disease. Based on own experience recent criteria from the literature, we consider rituximab along with reduction of immunotherapy as a first-line therapy in PTLD